ELECTROLYTE-PLASMA TREATMENT UNDER NON-STATIONARY MODE IN A HIGH-GRADIENT ELECTRIC FIELD - Yu. G. Aliakseyeu; A. Yu. Korolyov; A. E. Parshuto; V. S. Niss (Наука и техника)
Electrolyte-plasma treatment has become widespread in the industry as an alternative to traditional chemical, electrochemical and mechanical methods of improving the surface quality of products made of metallic materials. Advantages ofelectrolyte-plasma treatment are a high intensity of microroughness smoothing, the use of low concentration salts solutions as electrolytes, the possibility of processing products of complex shape. The main disadvantage of this method is high power consumption, so the method can be considered in its classical form to the power-consuming. A possible way of reducing power consumption is treatment in unsteady modes that arise in the transition zone between a switching and stable electrolyte-plasma treatment process and is characterized by the periodic formation of a stable vapor-gas shell and a transition to an electrochemical process. The paper presents the results of a study of the influence of a high-gradient electric field under unsteady electrolyte-plasma treatment modes on the energy parameters of the process and the characteristics of the surface being treated. It is established that a high-gradient electric field has a significant effect on the decrease in specific power consumption, which is explained by a decrease in losses in the electrolyte and the influence of the field on the formation and maintenance of the vapor-gas shell. As a result of the study of the effect of a high-gradient electric field in unsteady EPT modes on characteristics of the surface layer was established that a significant impulse current density in the zone of predominantly electrochemical treatment leads to a selective etching of the surface and the formation of a characteristic micro relief of the surface with a developed porous microstructure with pore sizes from 0.3 to 2.5 microns. The most pronounced porous microstructure is provided at a voltage of 270–300 V and an additional inductance of 3.2 mH.